Narratives of global convergence and the power of choosing a measure. (2nd January 2020) - Greenstein, Joshua
ABSTRACT: Research into the use of indicators in global governance emphasises the importance of which types of quantitative measurements of social phenomena are chosen, how they are chosen, and by whom. I contribute to this literature by applying these concepts to inequality measurements in the context of global income distribution. Any discussion of inequality includes an implicit normative comparison of distributions and the choice of measure will affect these comparisons. I argue that these seemingly technical methodological choices are actually value-laden, and may have effects on public perceptions and even policy outcomes. In particular, I focus on some influential research results concerning global income distribution and illustrate how a change in measurement choice can put these familiar findings in a new light. I also make a contribution by applying the concepts used to evaluate pro-poor growth – usually reserved for within country studies – to the question of global between-country convergence.